(untitled) (Medico Legal Update, 2021)
Introduction: The literature on burnout research shows that more than 90% have used the Maslach Burnout Inventory (MBI). Objective: The aim is to establish the psychometric properties in terms of reliability, sensitivity and validity of the Maslach Burnout Inventory (MBI) and to adapt it to the context of Moroccan teachers. Method: This work was carried out through a process of translation and reverse translation of the original instrument by adapting the elements to the teaching profession. To determine the psychometric characteristics, we used Cronbach’s alpha to determine reliability, exploratory factor analysis to extract factors and determine dimensionality, and confirmatory factor analysis to test the validity of the statistical model. Validation of the instrument was carried out on a sample of 170 teachers working in public schools in Ouezzane region (Morocco). Results: Items 4, 5, 7, 9, 12, and 22 were relatively incoherent with respect to the other items, they were eliminated. The factorial analysis made appear three factors whose are explain 58.22% of the total variance. Cronbach’s ? for the whole questionnaire (0.761), for emotional exhaustion (0.819), depersonalization (0.850) and sense of personal accomplishment (0.785). The confirmatory factor analysis (CFA) showed satisfactory adjustment indices (X2 = 164,938 - df = 101- CFI = .937 - TLI = .915 - RMSEA = .037- P close = .984). Conclusion: We propose to use Maslach’s Theoretical Model for the Moroccan Sample in Future Research on the burnout of Moroccan teachers.